The Influence of Image Media on Student Learning Outcomes on the Theme of the Beautiful Togetherness of Class IV State Primary School 101735 Sei Semayang - Situmorang, Tioro; Tanjung, Darinda Sofia; Simarmata, Ester Julinda; HS, Dyan Wulan Sari; Juliana, Juliana (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2024)
This research aims to determine the influence of image media on student learning outcomes on the theme of the beauty of togetherness for class IV SD Negeri 101735 Sei Semayang for the 2022\2023 academic year. In this study, a quantitative method was used, the population of this study was class IV students at SD 101735 Sei Semayang, totaling 30 students. The results of this research show that before being given treatment students had an average learning outcome of 58 and did not meet the KKM and after being given treatment students had an average learning outcome of 88.6. With normality test results of 0.117, the conclusion is that the data is normally distributed. The correlation test result is 0.638, which means rcount (0.740)> rtable (0.361), so Ha is accepted. So there is a strong influence between the use of image media on student learning outcomes in class IV of SD Negeri 101735 Sei Semayang. It can be seen from the results of the t-test research where tcount>ttable is 5.816>2.042 so it can be stated that Ha is accepted. This shows that there is a significant positive influence from the use of image media on student learning outcomes on the theme of the Beauty of Togetherness for Class IV of SD Negeri 101735 Sei Semayang for the 2022\2023 academic year.